Feminism in Selected American Movies: A Critical Discourse Analysis - Sarah Hatem Jaddoa; Haya Abdulsalam Jasim (مجلة الباحث, 2025)
This study investigates the depiction of female figures in productions like “ Thelma & Louise (Scott, 1991) and “Hidden Figures (Melfi, 2016). It aims to examine how the main characters in these selected movies employ language as an instrument of resistance and solidarity, and to analyze how patriarchal and academic power frameworks are recreated and challenged via texts within the movies. To achieve these aims, this research adpots Fairclough’s three categories of model of CDA, that investigates discourse based on textual level (lexical choice and grammatical frameworks), discursive level (output and explanation of dialogue), and the social level (ideological and authoiry-based embodiment).“Thelma & Louise (Scott, 1991)” mainly concerned on heroines’ evolution from confronting obstacle to take charge of their lives. The movie provokes inquiries about conventional anticipations of manner of women, arousing notable arguments on feminism’s independence. The reaction of audiences indicates the influence of these movies in constructing hypotheses on these problems. At the same time